On the Pricing of Mandatory DCF Disclosures: Evidence from Oil and Gas Royalty Trusts - Patatoukas, Panos N.; Sloan, Richard G.; Zha, Jenny (The Accounting Review, 2015)
ABSTRACT We identify a setting in which firms are required to disclose discounted cash flow (DCF) estimates relating to the value of their primary assets. ASC 932 (formerly SFAS No. 69) has mandated DCF disclosures for proved oil and gas reserves since 1982, and these reserves constitute the primary assets of oil and gas royalty trusts. For a hand-collected sample of oil and gas royalty trusts, we find that (1) the mandatory DCF disclosures are incrementally value-relevant over historical cost accounting variables, (2) investors misprice royalty trust units because they underweight the disclosed DCF estimates when forecasting future distributions, and (3) media articles bringing attention to discrepancies between price and the disclosed DCF estimates are significant stock price catalysts. While our evidence indicates that mandatory DCF disclosures can be incrementally useful for security valuation, it also indicates that investors may overlook such information, potentially due to lack of attention and accounting expertise. Data Availability: Data are publicly available from sources indicated in the text.